Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Bourassa, Mark A.; Meissner, Thomas; Cerovecki, Ivana; Chang, Paul S.; Dong, Xiaolong; De Chiara, Giovanna; Donlon, Craig; Dukhovskoy, Dmitry S.; Elya, Jocelyn; Fore, Alexander; Fewings, Melanie R.; Foster, Ralph C.; et al. (Frontiers in Marine Science, 2019)
Strengths and weakness of remotely sensed winds are discussed, along with the current capabilities for remotely sensing winds and stress. Future missions are briefly mentioned. The observational needs for a wide range of wind and stress applications are provided. These needs strongly support a short list of desired capabilities of future missions and constellations.